Effect of nitrogen and farmyard manure on yield and nutrient uptake of turmeric (Curcuma longa) and different forms of inorganic N build-up in an acidic Alfisol of Meghalaya - MAJUMDAR, B; VENKATESH, M S; KUMAR, KAILASH (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during 1999 and 2000 to study the effect of different levels of nitrogen and farmyard manure on yield, nutrient uptake by turmeric (Curcuma Longa L.) and residual build-up of various forms of N in an Ultic Hapludalf. The rhizome and straw yields, P and K uptake by turmeric increased signficantly up to 90 kg N/ha, however incresase in N uptake was significant up to 150 kg N/ha. Nitrogen-use efficiency was maximum (34.3%) at 30 kg N/ha and decreased progressively with increasing N levels. Addition of fertilizer N and farmyard manure significantly enhanced the available, NH 4 + NO3 - and mineral N and available P and K and N150 F5 treatment registered the highest values of these properties in post-harvest soil. Net gain in the available N content. in post-harvest soil was higher (27.1 kg/ha) when N was applied along with farmyard manure. A combination of 90 kg N with 5 tonnes farmyard manure/ha was optimum for turmeric production with considerable nutrient build up in acid soil.